SIMULASI UNJUK KERJA PLTS 1 MW KAYUBIHI JIKA MENGGUNAKAN SUN TRACKING SYSTEM - Wiranata, I.P.A.; Kumara, I.N.S.; Sukerayasa, I.W. (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i04.p2, 2019)
The Kayubihi PLTS is a PLTS with a capacity of 1 MWp. The Kayubihi PLTS solar module is installed in a fixed configuration, installed facing north with a tilt angle from the ground surface of 15 °. In a condition without a tracker, the Kayubihi PLTS generates an annual energy of 1656.2 MWh. In this paper a simulation will be carried out to find out how much energy the PLTS Kayubihi has when it has a sun tracker system installed. This tracker system simulation will be made in 2 scenarios. Scenario 1 uses a single axis tracker system where the solar module will move to follow the sun from east to west. Scenario 2 Kayubihi PLTS is equipped with a multi axis tracker system that moves in the direction of the sun from east to west and north to south. Simulations using a single axis tracker system produce annual energy of 2096.1 MWh. While simulations using the multi axis tracker system produce an annual energy of 2159.8 MWh. When compared with existing conditions, the use of a single axis tracker system gets an increase in energy of 439.9 MWh and if using a multi axis tracker system an energy increase of 503.6 MWh is obtained. The annual energy difference in the single axis tracker system with the multi axis tracker system is 63.7 MWh. The total cost of installing a single axis tracker system is Rp. 560,000,000 with 70 units of tracker and installing a multi axis tracker system amounting to Rp. 700,000,000. A total of 70 units of tracker. Keywords: Kayubihi PLTS, Single Axis Tracker System, Multi Axis Tracker System. At the results of the simulation of electricity sales, the tracker system is more profitable than the system without a tracker.